1975
DOI: 10.1007/bf02532360
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of renal medullary lipid droplets from normal, hydronephrotic, and indomethacin treated rabbits

Abstract: Lipid droplets isolated from rabbit renal medullary tissue were analyzed and found to be composed of triglyceride and free fatty acids in a ratio of 2.9:1. These triglycerides were unique when compared to triglycerides of other rabbit tissues examined, in that they contained high percentages of octadecanoic acid (stearic acid, 9.8%), 5,8,11,14-eicosatetraenoic acid (arachidonic acid, 6.8%), and 7,10,13,16-docosatetraenoic acid (adrenic acid, 10%). Lipid droplet triglycerides were found to increase during exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1977
1977
1983
1983

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…A marked increase in the number and the triglyceride content of the renal medullary interstitial cell lipid droplets and a decreased rate of PGF, synthesis have been observed with either ureter obstruction or indomethacin treatment in rabbits (11,12). Contradictory data, however, are available in the rat (13), where a reduction of lipid granularity of interstitial cells was observed with indomethacin.…”
Section: Resultsmentioning
confidence: 99%
“…A marked increase in the number and the triglyceride content of the renal medullary interstitial cell lipid droplets and a decreased rate of PGF, synthesis have been observed with either ureter obstruction or indomethacin treatment in rabbits (11,12). Contradictory data, however, are available in the rat (13), where a reduction of lipid granularity of interstitial cells was observed with indomethacin.…”
Section: Resultsmentioning
confidence: 99%
“…These highly specialized cells exist in high density in the renal medulla and papilla (16,17), and contain large amounts of arachidonic acid, the precursor of PGE2 biosynthesis (18).…”
mentioning
confidence: 99%
“…Comai et al [2,3] showed a decrease in PGF2a synthesis of hydronephrotic rabbits. However, in the present study, renal PGF2a remained significantly unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies on some aspects of renal PGs in hydronephrosis [1][2][3][9][10][11]. Thus, Olsen et al [11] showed that an increased intrapelvic pressure stimu lated renal PG activity.…”
Section: Introductionmentioning
confidence: 99%